Effectiveness and safety of Chinese herbal footbaths as an adjuvant therapy for dysmenorrhea: a systematic review and meta-analysis - Tian, Xiaoping; Wei, Jingwen; Zhuang, Yijia; Lin, Xiaoding; Liu, Liu; Xia, Jun; Huai, Wenying; Xiong, Ying; Chen, Yunhui (Frontiers in Pharmacology, 2024)
Objectives: To evaluate the effectiveness and safety of Chinese herbal footbaths (CHF) as an adjunctive therapy in managing dysmenorrhea. Methods: Ten electronic databases were searched to identify eligible randomized clinical trials (RCTs) from inception until June 2023. Outcome measurements encompassed the total effective rate, visual analog scale (VAS) score of pain intensity, Cox menstrual symptom scale (CMSS) score, symptom score, Traditional Chinese Medicine (TCM) syndrome scale, and any reported adverse events. The methodological quality of the included studies was assessed with the Cochrane collaboration tool. Review Manager 5.3 software was employed for quantitative synthesis, and funnel plots were utilized to evaluate potential reporting bias. Results: Eighteen RCTs with 1,484 dysmenorrhea patients were included. The aggregated results suggested that the adjunctive CHF could significantly ameliorate dysmenorrhea, as evident from the improved total effective rate [risk ratio (RR) 1.18, 95% confidence interval (CI): 1.12 to 1.23, P < 0.00001], VAS (MD 0.88, 95%CI: 0.68 to 1.09, P < 0.00001), CMSS (MD 3.61, 95% CI: 2.73 to 4.49, P < 0.00001), symptom score (SMD 1.09, 95%CI: 0.64 to 1.53, P < 0.00001), and TCM syndrome scale (MD 3.76, 95%CI: 2.53 to 4.99, P < 0.0001). In addition, CHF presented fewer adverse events with a better long-term effect (RR 1.34, 95%CI: 1.11 to 1.63, P<0.01) and diminished recurrence rate (RR 0.19, 95%CI: 0.09 to 0.39, P<0.0001). Conclusion: Current evidence implies that CHF may be an effective and safe adjunctive therapy for patients with dysmenorrhea. However, the methodological quality of the studies included was undesirable, necessitating further verification with more well-designed and high-quality multicenter RCTs.